Chlorella sp. inoculum doses affect ethinylestradiol removal in a wastewater treatment plant in the Peruvian Andes - Chávez Collantes, Azucena (2025)
The microalgae Chlorella sp. have demonstrated efficiency in the removal of pharmaceutical contaminants. However, there is no agreement on the inoculum dose since it depends on the contaminant concentration and other very specific parameters in each case. This study aims to evaluate the effect of Chlorella sp. inoculum doses on ethinylestradiol (EE) removal from wastewater treatment plant effluent in Celendín district of the province of Celendín, Cajamarca region, Peru. Four doses of inoculum (0, 100, 200, and 300 mL) were tested at a 2,1x10⁶ cell∙mL⁻¹ microalgae cell concentration and 4 mg∙L ⁻¹ of ethinylestradiol in photobioreactors. The final concentration of ethinylestradiol was determined after 20 days through High Performance Liquid Chromatography (HPLC). It was evidenced that a dose of 300 mL∙L ⁻¹ of Chlorella sp. could remove 96,49% of ethinylestradiol from wastewater, unlike the other tested concentrations, which were below 80,92% removal. It was concluded that at a higher dose of Chlorella sp. inoculum, a higher ethinylestradiol removal percentage was observed in a wastewater sample from a treatment plant in the Peruvian Andes.